TRANSLATION SHIFTS IN ENGLISH LITERARY PROSE: A LINGUISTIC PERSPECTIVE - Michael Johnson (International Journal of Literature and Language Studies, 2026)
This article investigates translation shifts in English literary prose from a linguistic perspective within the broader field of linguistics and applied language studies. The study uses selected parallel passages from English short fiction and their published translations into another language and applies contrastive analysis of lexical, syntactic, semantic, and stylistic shifts. The main finding is that the most common shifts involved sentence segmentation, cultural specification, tense-aspect adjustment, and changes in metaphor intensity. The article argues that translation should be viewed as a linguistic negotiation between structural possibility and literary effect. The discussion is relevant to researchers, teachers, curriculum designers, and graduate students who need concise but systematic models of linguistic inquiry.